2018
DOI: 10.1111/1468-4446.12382
|View full text |Cite
|
Sign up to set email alerts
|

‘No one to trust’: the cultural embedding of atomism in financial markets

Abstract: The paper ethnographically explores the cultural embedding of atomistic indifference in online, global financial markets: arenas that have been digitally designed according to economic ideals and that demand an extreme form of relational and social dissociation from the partners to exchange and from those affected by the transactions. Its case-study is lay financial-trading in Israel, a country undergoing extensive neoliberalization. The study shows that dissociation is embedded in an economic culture marked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This was originally due to the qualitative nature of the FoEL literature, using single-sited ethnographies and interviews, with the vast majority of studies conducted in the UK and the US. These were later complemented by studies outside of these contexts, such as France (Lazarus, 2017), Italy (Di Feliciantonio, 2016), the Czech Republic (Samec, 2018), Poland (Lewicki, 2014), Hungary (Pellandini-Simanyi et al, 2015), Chile (Gonzalez, 2015), Israel (Ailon, 2019;Weiss, 2015), Argentine (Fridman, 2017), China (Maso, 2015), and Singapore (Lai, 2016(Lai, , 2017, among others.…”
Section: Geographies Of Financial Subjectivitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This was originally due to the qualitative nature of the FoEL literature, using single-sited ethnographies and interviews, with the vast majority of studies conducted in the UK and the US. These were later complemented by studies outside of these contexts, such as France (Lazarus, 2017), Italy (Di Feliciantonio, 2016), the Czech Republic (Samec, 2018), Poland (Lewicki, 2014), Hungary (Pellandini-Simanyi et al, 2015), Chile (Gonzalez, 2015), Israel (Ailon, 2019;Weiss, 2015), Argentine (Fridman, 2017), China (Maso, 2015), and Singapore (Lai, 2016(Lai, , 2017, among others.…”
Section: Geographies Of Financial Subjectivitiesmentioning
confidence: 99%
“…Other studies, in turn, showed that the neoliberal, financially perceptive and autonomous subject positions are embraced by people themselves (e.g. Cook et al., 2009; Fridman, 2017; Ailon, 2019; Roscoe, 2015). This suggests a mixed picture of willing vs reluctant financialisation across contexts and raises the question, not addressed so far due to the qualitative nature of these studies, of which of these relations to financialisation is more widespread.…”
Section: The Financialisation Of Everyday Life: the Ideal Financialised Subject Vs The Lived Experience Of Financialisationmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows, therefore, that organizations cannot be understood as morally toxic yet peopled by the occasional virtuous free spirit. Much current scholarship on morality in organizational settings would suggest just this, arguing that moral rectitude is dependent upon developing an individual, subjective ethical agency that is free from the corrosive restrictions of organizational accountabilities and bureaucratic structures (Ailon, 2019;Eggebø, 2013;Rhodes and Wray-Bliss, 2013). My account of the sociomaterial dimension of morality supplements Du Gay's (2000Gay's ( , 2008 spirited rehabilitation of Weber, a contrary voice in this debate.…”
Section: Discussion: Sociomateriality and Organizational Moralitymentioning
confidence: 86%
“…Strikingly, despite acknowledging that individuals engage with aspects of the investorial subject to a differing degree (Pellandini-Simanyi and Banai, 2020) and should not be categorised as 'risk-averse or passive' (Lai, 2017: 927) when not accumulating financial assets and choosing instead to invest in properties, a consequent conceptual development of differential subjectivities and practices into varied financial subject positions is missing. One underlying reasoning might be that qualitative studies have tended to focus on debt (Di Felicantono, 2016;Penaloza and Barnhart, 2011) or one aspect of asset ownership, such as homeownership (Pellandini-Simanyi et al, 2015;Samec, 2018) or non-professional trading (Ailon, 2019;Roscoe, 2015), without integrating a broader set of investment decisions. However, a holistic view of asset management is essential as can be seen in a recent study which revealed that distrusting financial investments did not translate into rejecting them but in an adjustment of the asset portfolio, excluding financial investments which are considered high risk and including non-financial investments which are seen as controllable due to being managed by oneself (Hillig, 2019b).…”
Section: 'Activity Of Conducting': the Everyday Investormentioning
confidence: 99%